Effect of Chandrasoor (Lepidium sativum) supplementation on performance of crossbred sows along with nursing piglets (Indian Journal of Animal Production and Management, 2023)
The present study was conducted at Pig Farm, Livestock Farm, Adhartal, College of Veterinary Science  & A.H., NDVSU, Jabalpur. A total of 14 crossbred sows (Large white yorkshire X Desi) just after farrowing  were randomly assigned to two different groups (Control and Chandrasoor), with seven sows in each group.  Individual sows along with piglets were maintained at farrowing pen. All the sows were fed the same gestation  diet during gestation. Diets were formulated as per ICAR (2013) standard. After the farrowing, sows of the  Chandrasoor group received 30 g Chandrasoor seed powder daily. Rest of the managemental schedule  was same for both the groups Piglets were weaned at 42 days of age. Significant differences (P
Keywords: Chandrasoor; Crossbred pigs; Piglets; Sows; Weight loss